2014
DOI: 10.1681/asn.2013070754
|View full text |Cite
|
Sign up to set email alerts
|

Association of Body Mass Index with Outcomes in Patients with CKD

Abstract: Obesity is associated with higher mortality in the general population, but this association is reversed in patients on dialysis. The nature of the relationship of obesity with adverse clinical outcomes in nondialysisdependent CKD and the putative interaction of the severity of disease with this association are unclear. We analyzed data from a nationally representative cohort of 453,946 United States veterans with eGFR,60 ml/min per 1.73 m 2 . The associations of body mass index categories (,20, 20 to ,25, 25 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
211
3
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 217 publications
(226 citation statements)
references
References 59 publications
9
211
3
3
Order By: Relevance
“…Considering the above evidence about the overwhelmingly deleterious effects of obesity on various disease processes, it is seemingly counterintuitive that obesity has been consistently associated with lower mortality rates in patients with advanced CKD [19,61] and ESRD [62,63]. Similar "paradoxical" associations have also been described in other populations, such as in patients with congestive heart failure [64], chronic obstructive pulmonary disease [65], rheumatoid arthritis [66], and even in old individuals [67].…”
Section: Mechanisms Of Action Underlying the Renal Effects Of Obesitymentioning
confidence: 91%
See 1 more Smart Citation
“…Considering the above evidence about the overwhelmingly deleterious effects of obesity on various disease processes, it is seemingly counterintuitive that obesity has been consistently associated with lower mortality rates in patients with advanced CKD [19,61] and ESRD [62,63]. Similar "paradoxical" associations have also been described in other populations, such as in patients with congestive heart failure [64], chronic obstructive pulmonary disease [65], rheumatoid arthritis [66], and even in old individuals [67].…”
Section: Mechanisms Of Action Underlying the Renal Effects Of Obesitymentioning
confidence: 91%
“…Furthermore, in numerous large population-based studies, higher BMI appears associated with the presence [8,12] and development of low estimated GFR [9][10][11][12][13], with more rapid loss of estimated GFR over time [14], and with the incidence of ESRD [15][16][17][18]. Elevated BMI levels, class II obesity and above, have been associated with more rapid progression of CKD in patients with pre-existing CKD [19]. A few studies examining the association of abdominal obesity using WHR or WC with CKD, describe an association between higher girth and albuminuria [20], decreased GFR [8] or incident ESRD [21] independent of BMI level.…”
Section: Association Of Obesity With Ckd and Other Renal Complicationsmentioning
confidence: 99%
“…Furthermore, in numerous large population-based studies, higher BMI appears associated with the presence 8,12 and development of low estimated GFR 9,10,13 , with more rapid loss of estimated GFR over time, 14 and with the incidence of ESRD [15][16][17][18] . Elevated BMI levels, class II obesity and above, have been associated with more rapid progression of CKD in patients with pre-existing CKD 19 . A few studies examining the association of abdominal obesity using WHR or WC with CKD, describe an association between higher girth and albuminuria 20 , decreased GFR 8 or incident ESRD 21 independent of BMI level.…”
Section: Association Of Obesity With Ckd and Other Renal Complicationsmentioning
confidence: 99%
“…Considering the above evidence about the overwhelmingly deleterious effects of obesity on various disease processes, it is seemingly counterintuitive that obesity has been consistently associated with lower mortality rates in patients with advanced CKD 19,61 and ESRD 62,63 . Similar "paradoxical" associations have also been described in other populations, such as in patients with congestive heart failure 64 , chronic obstructive pulmonary disease 65 , rheumatoid arthritis 66 , and even in old individuals 67 .…”
Section: Obesity In Patients With Advanced Kidney Disease: the Need Fmentioning
confidence: 99%
“…However, a recent report including half a million United States veterans with CKD showed that low BMI categories equally associate with those risks (5). A recurrent discussion in such association studies is that BMI, when used in isolation, gives distorted prognostic information.…”
mentioning
confidence: 99%